Covalent organic frameworks for membrane separations - Siow, Samuel Wei Jian (Nanyang Technological University, 2024)
The production of active pharmaceutical ingredients (APIs) relies heavily on solvents, requiring approximately 25 tons of solvents to produce one ton of APIs, with solvents accounting for 80-90% of the mass used in organic reactions and contributing to 80-85% of the waste generated. This dependency poses significant environmental and financial challenges due to the difficulties and expenses associated with safe disposal of waste solvents. Current waste management practices, such as waste-to-energy processes and distillation, are insufficient to fully address these issues. Membrane technology is an attractive alternative to conventional processes like distillation and liquid-liquid extraction due to its low carbon footprint, growing interest in waste treatment driven by high industrial waste generation and stricter discharge regulations, versatility in addressing global challenges, and potential to enhance resource efficiency, environmental sustainability, and product quality. However, developing solvent-resistant membranes with high permeability and selectivity remains essential as current OSN polymeric membranes struggle with stability and swelling in organic solvents. Covalent organic frameworks (COF) offer significant potential to be used as membranes for energy-efficient separation processes. COF membranes have demonstrated the ability to effectively separate nano-sized molecules based on size-selective transport through their well-ordered nano-pore structures. Particularly, COF membranes have shown promise in water treatment (nanofiltration; NF) and organic solvent nanofiltration (OSN), making them a focal point in recent research efforts. The current state-of-the-art COF-based membranes exhibited good membrane performances but are complex and difficult to fabricate on curve surfaces such as hollow-fibre substrates. COF mixed-matrix membranes offer easier fabrication but underutilize COF's crystalline properties. Hence, this study developed a novel method for COF membrane growth on the lumen of hollow-fibres and optimized the COF membranes for enhanced performance in chemical separations, water purification, and pharmaceutical applications. Key objectives include optimizing COF membrane fabrication, enhancing membrane compatibility, maximizing COF membrane potential, and tailoring them for high permeability, selectivity, and stability across various separation processes, notably in organic solvent environments and pharmaceutical applications. This thesis discusses in detail the existing state-of-the-art, fabrication, characterization, and performance of the crystalline porous covalent organic framework used in membrane separations. The grafting and synthesis of COF on a modified tubular alumina substrate were investigated, followed by its physiochemical characterizations, leading to the membrane performance studies which include aqueous nanofiltration (NF), OSN, loose nanofiltration (LNF), and active pharmaceutical ingredient (API) separations. Chapters 1 and 2 provide an overview of the background information, challenges in membrane-based separations, and a literature review about COF and their physiochemical properties, fabrication techniques of COF-based membranes, and membrane separation applications. Chapter 3 focuses on two surface-modifying agents, namely, 3-aminopropyltriethoxysilane (APTES) and polydopamine (PDA) on alumina ceramic membranes for the development of COF thin-film membranes. The COF thin film membranes were synthesized using room temperature in situ synthesis, and two specific COF, TpPa-1 and TpPa2Me, were investigated. The performance of these membranes was evaluated through both aqueous and solvent filtration studies. Moreover, the robustness of the COF membranes was comprehensively examined, considering their resistance to changes in pressure and solute concentration. Chapter 4 presents a novel vapor/vapor-solid (V/V-S) method to fabricate a COF membrane on the inner lumen surface of the porous polydopamine-modified ceramic hollow fiber. The V/V-S method making use of the vapor/vapor interaction of the two precursors of the COF is a one-step, fast, and scalable process to fabricate high-quality COF membranes within a short reaction time of 8 h, producing membranes around 100 nm thick with strong adhesion to the substrate. The dilute monomer reaction strategy of the V/V-S can grow highly crystalline COF on curved surfaces specifically the lumen of alumina hollow-fiber membranes. Advanced membrane separation applications both in LNF and OSN were demonstrated with cross-flow profile and inside-out configuration. The crystalline TpPa-1 membrane demonstrated remarkably high permeance for both water and organic solvents, while also maintaining excellent dye rejection over extended periods. Chapter 5 introduces an extension of the V/V-S method through thermal cycling, offering precise control over COF membrane thicknesses ranging from 100 to 500 nm. This approach involves introducing fresh COF precursors in the vapor phase, providing a controlled method for tuning membrane thickness. Additionally, the method introduces promise for extending to other COF with various sizes and precursor compositions, such as TpPa2Me, TpPa2Cl, and TpHz, thus expanding the range of materials applicable for membrane design and fabrication. Notably, different COF, including TpPa-1, TpPa2Cl, and TpHz, maintained consistent Molecular Weight Cut-Off (MWCO) values (~700, 600, 550 Da). Our reported TpPa2Cl/alumina membrane fabricated with 1-3 cycles exhibited high API GA rejection rates of 90%, 95%, and 98%, alongside excellent DMSO permeance of 20, 18, and 15 L m−2 h−1 bar−1. This chapter illustrates the efficacy of COF membranes in achieving both high selectivity and permeance in OSN applications targeted at API separation. This advancement represents a significant step forward in the development of COF membranes, enhancing their properties and functionalities for diverse separation applications. In Chapter 6, the conclusions and outlook for COF membranes in advanced separations are discussed. The focus is on underlining the versatility of COF membranes and introducing the V/V-S method for COF growth and performance enhancement. The need for ongoing investigations and developments underscores the commitment to advancing COF membrane technology for more effective and widespread applications in separation processes. In summary, this thesis addresses the challenges associated with solvent waste and the limitations of current membrane technologies through the development and implementation of advanced solvent-resistant membranes with high permeability and selectivity. By significantly contributing to the advances in membrane fabrication using COF materials, particularly in NF, LNF, and OSN applications. The research includes developing surface modifications, novel fabrication techniques, and evaluating COF materials, resulting in membranes that demonstrate exceptional separation performance. These findings contribute valuable insights, optimizing separation efficiency and paving the way for more energy-efficient and economically viable applications in the future.